2011
DOI: 10.1001/archinternmed.2011.497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Behavior Support Intervention for Patients With Poorly Controlled Diabetes

Abstract: clinicaltrials.gov Identifier: NCT00668590.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
186
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(190 citation statements)
references
References 18 publications
1
186
1
2
Order By: Relevance
“…33,49,50,54,55 While we did find that all participants had improvements in A1C at 3 months, this improvement was not sustained at 6 months. Participants may not have maintained the skills they gained after the weekly contact ended.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…33,49,50,54,55 While we did find that all participants had improvements in A1C at 3 months, this improvement was not sustained at 6 months. Participants may not have maintained the skills they gained after the weekly contact ended.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies testing diabetes self-management interventions have had mixed results in impacting diabetes self-care activities. 49,50 Considering that Latinos tend to struggle with lifestyle changes due to competing demands and lack of resources for lifestyle change, our study demonstrated the possibility of a church-based diabetes self-management intervention helping participants overcome their struggles in making behavior change. 12,51 Even though these outcomes are self-reported, these findings are increasingly relevant since recent studies, including LOOK AHEAD, note that improvements in diet and exercise translate to improvements in many patient-centered outcomes, such as functional status and quality of life.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This left a total of 35 articles included in the review. There were 15 (43%) descriptive or observational studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), 4 (11%) design or development studies (28-31), 3 (9%) quasi-experimental studies (2,32,33), 7 (20%) randomized controlled trials (34)(35)(36)(37)(38)(39)(40), and 6 (17%) qualitative studies (41)(42)(43)(44)(45)(46) included in the review.…”
Section: Methodsmentioning
confidence: 99%
“…Connection is related to improved glycemic control (34), improved depression and quality of life (35), and reductions in HbA1C (31,36,38). In general connection is correlated with self-care activities in adolescents (30), improves weight loss through a telephone intervention (37), and is experienced when a family member remains vigilant (43).…”
Section: Selected Findingsmentioning
confidence: 99%